Memristor Arrays: Associative Memory for Image Recovery with a High‐Performance Memristor Array (Adv. Funct. Mater. 30/2019). (23rd July 2019) - Zhou, Ying; Wu, Huaqiang; Gao, Bin; Wu, Wei; Xi, Yue; Yao, Peng; Zhang, Shuanglin; Zhang, Qingtian; Qian, He
Abstract : Among the basic functions of the brain, associative memory is an important ability, as widely illustrated by Pavlov's dog experiment. In article number1900155, by employing an electro‐thermal modulation layer, Huaqiang Wu and co‐workers optimize a multilevel memristor cell. A Hopfield neural network is experimentally demonstrated on an integrated 1 k memristor array.